General discussion - Ewart, Gordon (Scottish Archaeological Internet Reports, 2001)
The results of the excavation have been expressed as a simple sequence of building, repair and decline, but clearly also demonstrate the evolution of the house within key historic periods. In discussing the significance of the findings, evidence of this evolution is reviewed in terms of specific episodes of construction work on the site. There are three historical periods against which the episodic development of the buildings within the abbey complex can be best reviewed, in as much as prevailing conditions enable the abbey to be successful, and which also more acutely prescribed and determined the scale and nature of the changes to the buildings. The historical periods are as follows: consolidation and early success in the 12th to the later 13th century; remodelling in the 14th century, and commendatorship in the 15th century.